New Medical Device May Promote Long-Term Weight Loss - Vinall, Phil (MD Conference Express, 2014)
The incidence of obesity is increasing across the world. By 2020, obesity is expected to affect 672 million individuals, including 149 million in the United States. This article discusses a novel restrictive bariatric medical device called the Onciomed Gastric Vest System.